Online student engagement as formative assessment - Kawase, Ricardo; Parmaxi, Antigoni (My University, 2014)
While in traditional learning scenarios, formative assessment relies solely on the judgment of teachers, technology enhanced learning provides means for automatically identifying room for e ective learning improvement. Given a digital learning environment and the support of learning analytics, it is possible to infer input for formative assessments. Teachers might be assisted by systems to adapt their teaching practice and to individually assess students. In this paper, we present evidence of this matter by reporting the experience of a teacher during a 13 week language course and by analyzing the students’ content production in an online environment during the same period
Keywords: Technology enhanced learning; Language development; Learning; Formative assessment